Improving Reading Comprehension of the Eleventh Grade Students of SMA Negeri 4 Palu Through the Use of Preview, Ask Question, Read and Summarize (PARS) Strategy - Renaldi, Laode Moh; Rofiqoh, Rofiqoh; Wahyudin, Wahyudin; Kamaruddin, Abdul (Datokarama English Education Journal, 2025)
The objective of this research was to determine whether the use of the PARS (Preview, Ask Question, Read, Summarize) strategy could improve reading comprehension among eleventh-grade students at SMA Negeri 4 Palu. A quasi-experimental design was used with a sample selected through available sampling. Class XI H served as the experimental group and Class XI F as the control group. Class XI H was chosen for treatment due to its lower English proficiency based on pre-test results. The research instrument was a reading test consisting of multiple-choice, essay, and true/false questions, administered as both pre-test and post-test. The mean pre-test scores were 46.04 for the experimental class and 47.46 for the control class. After treatment, the experimental group’s mean post-test score rose to 75.72, while the control group’s was 65.69. Statistical analysis showed that the t-counted value (1.99) exceeded the t-table value (1.67), indicating a significant improvement. The findings suggest that the PARS strategy effectively enhances students’ reading comprehension. Therefore, teachers are encouraged to implement this strategy to promote student engagement and understanding, particularly in content-heavy subjects, by guiding learners through an active and structured reading process.